Optical studies of non‐polar m‐plane (11¯00) InGaN/GaN multi‐quantum wells grown on freestanding bulk GaN. Issue 5 (20th January 2015) - Sutherland, Danny; Zhu, Tongtong; Griffiths, James T.; Tang, Fengzai; Dawson, Phil; Kundys, Dmytro; Oehler, Fabrice; Kappers, Menno J.; Humphreys, Colin J.; Oliver, Rachel A.
<x xml:space="preserve">Abstract</x> We report on the optical properties of non‐polar m‐plane InGaN/GaN multi‐quantum wells (MQWs) grown on ammonothermal bulk GaN substrates. The low temperature continuous wave (CW) photoluminescence spectra are broad with a characteristic low energy tail. The majority of the emission bands decay with a time constant ~300 ps, but detailed photoluminescence time decay and time resolved spectroscopy measurements revealed the existence of a distinct slowly decaying emission band. This slowly decaying component is responsible for the low energy tails observed in the CW spectra. Scanning electron microscopy–cathodoluminescence (SEM‐CL) studies show that the low energy emission band originates from regions across step‐bunches, which are associated to the GaN substrate miscut. Subsequent scanning transmission electron microscopy imaging demonstrates that semi‐polar QWs had formed continuous layers on the step bunches between the m‐plane QWs and were responsible for the slower decaying, low energy emission band. Thus we assign the asymmetric low energy emission tails observed in photoluminescence studies to the formation of semi‐polar facet QWs across the step bunches associated with the GaN miscut.